Peptide CyRL-QN15 alleviates UVB-induced skin aging by promoting the repair of barrier - Zijian Kang; Saige Yin; Xiaoya Han; Xin Liu; Ying Peng; Qiuye Jia; Zhe Fu; Yuansheng Li; Yutong Wu; Zhaoxun Xiao; Zhiruo Li; Ying Wang; et al. (Ecotoxicology and Environmental Safety)
Skin photoaging, a process with substantial physical and psychological impacts, is also a recognized risk factor for skin cancer. Despite advancements in dermatological research, effective prevention and reversal of photoaging remain challenging. This study investigated the efficacy of CyRL-QN15, an optimized variant derived from the RL-QN15 peptide, in mitigating ultraviolet B (UVB)-induced skin photoaging in mice. Results showed that CyRL-QN15 promoted skin barrier repair and exhibited antioxidant and anti-apoptotic properties. Mechanistically, these effects were mediated by activating the downstream Wnt/β-catenin signaling pathway. Notably, the therapeutic efficacy of CyRL-QN15 was diminished by using the inhibitor MSAB, suggesting a crucial role for the β-catenin signaling pathway. Furthermore, CyRL-QN15 may exert its effects by binding to the Frizzled-8 receptor on the human keratinocyte (HaCaT) cell membranes. This study is the first to identify the role of β-catenin regulation in skin barrier dysfunction during photoaging, establishing a potential therapeutic foundation for targeting CyRL-QN15 to combat skin photoaging.